In Patients With Multiple Sclerosis, Both Objective and Subjective Sleep, Depression, Fatigue, and Paresthesia Improved After 3 Weeks of Regular Exercise - Sadeghi Bahmani, Dena; Kesselring, Juerg; Papadimitriou, Malamati; Bansi, Jens; Pühse, Uwe; Gerber, Markus; Shaygannejad, Vahid; Holsboer-Trachsler, Edith; Brand, Serge (Frontiers in Psychiatry, 2019)
Background: Multiple Sclerosis (MS) patients suffer various difficulties including sleep complaints, symptoms of depression and fatigue, paresthesia, and cognitive impairments. There is growing evidence that regular physical activity has a positive effect on both sleep and psychological functioning, though there is limited evidence of this kind for MS patients. The aim of the present study was therefore to investigate the impact on this patient group of a regular exercise program with respect to subjective and objective sleep, depression, paresthesia, fatigue, and cognitive performance. Methods: A total of 46 patients (mean age: 50.74 years; EDSS: 5.3, 78.4% females) completed this three-week intervention study. At baseline and three weeks later, they answered questionnaires covering, sociodemographic information, subjective sleep, depression, fatigue, paresthesia, and subjective physical activity. Objective sleep (sleep electroencephalogram EEG recordings) and cognitive performance were also assessed at both time points. Patients participated in a regular exercise activity every weekday for about 60 minutes. Results: Compared to the baseline, by the end of the study objective sleep had significantly improved (sleep efficiency; sleep onset latency; wake time after sleep onset), and symptoms of sleep complaints, depression, fatigue, ​and paresthesia were significantly reduced. Subjective physical activity (moderate and vigorous) and cognitive performance also increased over the course of the intervention. Conclusions: In patients with MS, participation in regular exercise impacted positively on their objective and subjective sleep, depression, paresthesia, fatigue, and cognitive performance.